2017
DOI: 10.1108/ijhcqa-09-2016-0124
|View full text |Cite
|
Sign up to set email alerts
|

Applying adult development theories to improvement science

Abstract: Structured Abstract:Purpose: This article addresses how adult development theories can contribute to quality improvement. Design/Methodology/Approach: A theoretical analysis and discussion on how personal development empirical findings can relate to quality improvement (QI) and Deming's four improvement knowledge domains. Findings: Adult development research shows that professionals have qualitatively diverse ways of meaning-making and ways to approach possibilities in improvement efforts. Therefore, professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Empirically based theories depict a transformation process in the structures of meaning making, and the process involves qualitatively different changes resulting in increasing hierarchical complexity (Hoare, 2011). These cognitive competencies develop throughout adult life and have strong predictive validity in relation to a wide range of issues in working life, such as competence at work and leadership effectiveness (Dawson and Heikkinen, 2009; Kegan, 1994; Kjellström and Andersson, 2017; Kjellström and Stålne, 2017; McCauley et al., 2006; Rooke and Torbert, 2005; Torbert, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Empirically based theories depict a transformation process in the structures of meaning making, and the process involves qualitatively different changes resulting in increasing hierarchical complexity (Hoare, 2011). These cognitive competencies develop throughout adult life and have strong predictive validity in relation to a wide range of issues in working life, such as competence at work and leadership effectiveness (Dawson and Heikkinen, 2009; Kegan, 1994; Kjellström and Andersson, 2017; Kjellström and Stålne, 2017; McCauley et al., 2006; Rooke and Torbert, 2005; Torbert, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…17 37 Previous research has shown that children value taking part in these kinds of activities. 38 The staff experienced challenges to improvement work, and they tested improvement tools but did not find them entirely appropriate for their work, because they preferred existing methods for reflection.…”
Section: Discussionmentioning
confidence: 99%
“…When initiating a QI initiative, there are assumptions that the staff involved have enough skills to adopt the competences needed, but some competences connected to QI efforts can also be developmental challenging. 38 Thus, there seem to be challenges in using QI interventions and tools in new contexts. 39 Regarding improvement tools, the message seems to be clear: the preschool staff had tried these tools but did not continue to use then and/or will not continue to use them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, systems knowledge includes the understanding of dynamic changes and is challenging to achieve. It involves a 'development capacity' that requires a deeper kind of learning as double loop learning and second order learning (Kjellström & Andersson, 2017). Double-loop learning requires a shift in understanding, from simple and static to broader and more dynamic, such as taking into account the changes in the surroundings and the need for expressing changes in mental models (Argyris, 2002).…”
Section: Discussionmentioning
confidence: 99%